Cancer care and occupational therapy: A scoping review. (19th January 2020) - Wallis, Amy; Meredith, Pamela; Stanley, Mandy
Abstract: Introduction: Cancer can disrupt participation in everyday activities, suggesting a place for occupational therapy; however, there is a need to articulate the nature, scope and available evidence supporting the occupational therapy role within cancer care. In this scoping review, we identify the breadth of practice and evidence for occupational therapy in cancer care, across all stages of the disease trajectory (diagnosis to palliation/survivorship) throughout the lifespan. Methods: Five electronic databases were searched in June 2018, for English language articles. Key words were: cancer care, OR oncolog*, OR oncologic care, OR neoplasms, OR cancer survivors, OR terminal cancer, OR cancer rehabilitation, AND occupational therap*. No date restrictions were imposed. Included were: all styles of literature including grey literature, all types of cancers and all age brackets. There were no restrictions on place of origin of papers. Following the Arksey and O'Malley (2006; International Journal of Social Research Methodology, 8 : 19–32) framework for scoping reviews, the first author screened titles and abstracts, and all three authors reviewed sets of the included articles. Conflicts were discussed until consensus was reached. Results: After evaluating 305 titles and abstracts and 111 full‐text articles, 89 papers were retained. Articles included research studies ( n  = 43), reviews ( n  = 15), grey literature ( n  = 16), practice analyses ( n  = 14) and an editorial ( n  = 1). The occupational therapy roles described were diverse, but largely descriptive in nature, with little evidence of outcomes from treatment. Furthermore, the majority of papers addressed adult populations, with few considering children, adolescents or young adults. Most papers focused on specific stages of the disease, and none addressed the disease along its full trajectory. Conclusion: Despite identifying a diverse range of occupational therapy roles in cancer care throughout the disease trajectory and across the lifespan, the need for professional discourse and research within our profession was highlighted. This was particularly evident for adolescents and young adults with cancer.